Test-re-test reliability and dynamics of the Fukuda–Unterberger stepping test - Hemm, Simone; Baumann, Denise; Duarte da Costa, Vasco; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2023)
Background: The Fukuda-stepping-test (FST), i.e., repetitive walking on the spot while blind-folded, has been proposed as a means to assess the integrity of the vestibular pathways. While its sensitivity to detect abnormalities in patients is limited, it may be useful in studying the physiol-ogy of the subjective-straight-ahead (SSA). Considering reported systematic shifts in SSA in humans, we hypothesize that such asymmetries arise from individual differences in the orienta-tion/configuration of the macular organs and in central processing of vestibular input. We hypoth-esize that such asymmetries are stable over time in individual subjects. Alternatively, such asymmetries may arise from random noise in the sensory/motor systems involved, demonstrat-ing low reproducibility over time. Material and methods: 24 subjects walked on the spot over 60 seconds while blindfolded (n=6 trials per subject). Using an inertial measurement unit (IMU) placed at the chest, angular devia-tions were recorded and compared to manually-measured final positions. Both static (direction, magnitude) and dynamic (time-to-onset of deviation, pattern of deviations) parameters were re-trieved from the yaw slopes. Results: Significant deviations were found in 15/24 participants for the manual measurements (leftwards=8; rightwards=7), whereas when using the IMU-sensor 13/24 participants showed significant shifts (leftwards=9; rightwards=4). There was a high correlation (0.98) between man-ually measured rotation angles (average absolute deviations=58.0 deg±48.6 deg; intra-individual variability=39 deg±24 deg) and sensor-based yaw slopes (1.00 deg/sec±0.88 deg/sec; 0.67 deg/sec±0.41 deg/sec). Relevant yaw deviation was detected 22.1 sec±12.3 sec (range=5.6 sec-59.2 sec) after the onset of marching (no relevant yaw-deviation in 15/139 measurements), showing a mostly linear behavior over time. Conclusion: We observed significant inter-individual variability in task performance in the FST, reproducing findings from previous studies. With test-re-test reliability being moderate only, but at the same time observing a preference in the side of shifts in most trials and subjects, we con-clude that likely both individually varying estimates of straight-ahead and random noise contribute to the pattern of angular deviations observed. Using an IMU-sensory based approach, additional dynamic parameters could be retrieved, emphasizing the value of such a quantitative approach over manual measurements. Such an approach may provide useful additional information to dis-tinguish patients from healthy controls.